2020
DOI: 10.1186/s13613-020-0645-1
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term renal outcomes following severe rhabdomyolysis: a French multicenter retrospective study of 387 patients

Abstract: Background: Rhabdomyolysis is a life-threatening disease that can lead to severe hyperkalemia, acute kidney injury (AKI) and hypovolemic shock. The predictive factors of AKI and acute to chronic kidney disease (CKD) transition remain poorly described. Methods: This multicenter retrospective study enrolled 387 patients with severe rhabdomyolysis (CPK > 5000 U/L). Primary end-point was the development of severe AKI, defined as stage 2 or 3 of KDIGO classification. Secondary endpoints included the incidence of AK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
60
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 26 publications
(40 reference statements)
4
60
2
3
Order By: Relevance
“…The majority of studies in patients with rhabdomyolysis focused on risk factors or prediction of AKI and RRT (3,10,11), but the RRT duration is not always reported. Even a Cochrane review on continuous RRT for rhabdomyolysis did not include RRT duration as an outcome of interest (12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of studies in patients with rhabdomyolysis focused on risk factors or prediction of AKI and RRT (3,10,11), but the RRT duration is not always reported. Even a Cochrane review on continuous RRT for rhabdomyolysis did not include RRT duration as an outcome of interest (12).…”
Section: Discussionmentioning
confidence: 99%
“…However, the French investigators showed that 30% had significant residual impairment. Progression to advanced CKD (eGFR < 30 ml/min/1.73 m 2 ) was also relatively common (11). A smaller study by Rodriguez et al reported that RRT was maintained for 8.3 (range, 2-21) days in 12 patients who needed RRT (of 73 patients with AKI), and no patient remained dialysis-dependent at discharge (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can cause severe morbidity and mortality from cardiac arrhythmia, hypovolemia, acute kidney injury, electrolyte imbalances and metabolic acidosis if left untreated [5]. A CPK cut-off value of 5000 U/L has been proposed to indicate the risk of developing AKI or death [6].…”
Section: Discussionmentioning
confidence: 99%
“…Renal replacement therapy was indicated as the renal function, metabolic acidosis and electrolyte derangements failed to improve with initial therapy. A review article by Chavez et al noted that, despite the improvements in myoglobin and electrolyte concentrations in patients treated with haemofiltration, the mortality rates of up to 59% with severe forms of rhabdomyolysis remained unchanged [ 1 , 2 ] . This was the case for our patient who developed an upper gastrointestinal bleed after haemofiltration, which was a likely combination of DIC and hepatic impairment that culminated in an unfavourable outcome.…”
Section: Discussionmentioning
confidence: 99%